Peningkatan Kapabilitas Organisasi melalui Pendampingan Implementasi Gerakan Sumsel Mandiri Pangan (GSMP) - Atrika Iriani; Bambang Suprianto (Jurnal Kabar Masyarakat, 2024)
The South Sumatra Independent Food Movement (GSMP) Mentoring aims to improve the organizational capabilities of farmer communities in South Sumatra, through improving Organizational Capability. The main problem faced is the suboptimal field assistance related to plant and fish cultivation. A participatory approach is applied through socialization, formation of working groups, identification of needs, preparation of action plans, training, and technical assistance, as well as development of market access. The results of the study showed a significant increase in farmer welfare, marked by an increase in average income of 25%, an increase in food production of 20%, and strengthening local capacity. This program has also succeeded in increasing farmer access to agricultural technology and wider markets, in accordance with the theory of community empowerment, human capital, and market linkage. Recommendations for the sustainability of this program include the application of a participatory approach and ongoing assistance in other community empowerment initiatives